Prognostic impact of pan-immune-inflammation value and prognostic nutritional index in metastatic colorectal cancer patients treated with regorafenib - Yıldırım, Sedat; Alan, Özkan; Yıldız, Hacer Şahika; Doğan, Akif; Ay Ersoy, Seval; Odabaş, Hatice (The European Research Journal, 2025)
Objectives: Metastatic colorectal cancer (mCRC) remains a major cause of cancer-related mortality, with limited therapeutic options available after the failure of standard treatments. Regorafenib, an oral multichines inhibitor, has shown a survival advantage in treatment refractory mCRC. This research aims to evaluate the real-world effectiveness of regorafenib and to investigate the prognostic significance of inflammatory and nutritional indicators, specifically the Pan-Immune-Inflammation Value (PIV) and Prognostic Nutritional Index (PNI). Methods: We conducted a retrospective analysis of 166 mCRC patients who received regorafenib 2014 to 2024. Demographic, clinical, and pathological data, treatment responses, and laboratory indicators were gathered. Survival outcomes were evaluated by Kaplan–Meier analysis, whereas prognostic variables were analyzed using Cox regression. Results: The average age was 58 years, and 59% of patients were male. The overall disease control rate with regorafenib was 33%, and the objective response rate was 11%. The median progression-free survival (PFS) was 3.8 months, and the median overall survival (OS) was 9.1 months. A high PIV (≥309.1) was associated with significantly shorter overall survival (7.1 vs. 11.8 months, P=0.001), whereas a high PNI (≥47.9) was correlated with longer overall survival (10.7 vs. 6.7 months, P=0.02). Multivariate analysis confirmed PIV and PNI as independent prognostic indicators. Conclusions: Regorafenib provides a modest survival advantage and disease stabilization in previously treated mCRC patients. PIV and PNI are independent prognostic biomarkers that may assist in patient stratification and therapy optimization. Further studies are warranted to refine predictive markers and dosing strategies.